SOSIAL EKONOMI DAN INDEKS MASSA TUBUH (IMT) PRIA DEWASA DALAM KAITANNYA DENGAN FAKTOR RISIKO PENYAKIT JANTUNG KORONER DI PERDESAAN DAN PERKOTAAN BOGOR-JAWA BARAT - Sri Anna Marliyati; Megawati Simanjuntak; Deni Surya Kencana (Food and Nutrition Society of Indonesia, 2010)
The objectives of this research was to study social economy and body mass index of men andit’s correlation with risk factor of coronary heart disease in rural and urban of Bogor, West Java. The amount of samples were 100 adult men aged 25-39 of years. Samples were devided into two categories of expense which as < Rp 500.000/capita/month (low income) and ³ Rp 500.000/cap/month,- (high income). Results of this study showed that using independent t-test there was a significant difference between low income and high income samples in rural area in the case of family size, education level, income per capita, total expenditure, nutritional knowledge score and HDL cholesterol level. In urban area, we found significance difference in the case of family size, education level, income per capita, total expenditure, total cholesterol level, LDL and HDL cholesterol level between low income and high income samples. Spearman rank correlation test in rural area showed significance correlation between education level, income per capita, total expenditure, and nutritional knowledge score with HDL cholesterol level. Income per capita and total expenditure correlated significantly with total cholesterol level and BMI correlated significantly with level of triglyceride. Meanwhile, in urban area we found significant correlation between education level, total expenditure, nutritional knowledge score, and BMI with total cholesterol level. Education level and nutritional knowledge score correlated significantly with LDL cholesterol level, and BMI correlated significantly with level of triglyceride.